Modeling and Simulation of Cadmium Removal from the Groundwater by Permeable Reactive Barrier Technology (Journal of Engineering, 2014)
The removal of cadmium ions from simulated groundwater by zeolite permeable reactive barrier was investigated. Batch tests have been performed to characterize the equilibrium sorption properties of the zeolite in cadmium-containing aqueous solutions. Many operating parameters such as contact time, initial pH of solution, initial concentration, resin dosage and agitation speed were investigated. The best values of these parameters that will achieved removal efficiency of cadmium (=99.5%) were 60 min, 6.5, 50 mg/L, 0.25 g/100 ml and 270 rpm respectively. A 1D explicit finite difference model has been developed to describe pollutant transport within a groundwater taking the pollutant sorption on the permeable reactive barrier (PRB), which is performed by Langmuir equation, into account. Computer program written in MATLAB R2009b successfully predicted meaningful values for Cd+2 concentration profiles. Numerical results show that the PRB starts to saturate after a period of time (~120 h) due to reduce of the retardation factor, indicating a decrease in percentage of zeolite functionality. However, a reasonable agreement between model predictions and experimental results of thetotal concentration distribution of Cd2+ species across the soil bed in the presence of zeolite permeable reactive barrier was recognized.